NALISIS MANEJEMEN RISIKO PEMBANGUNAN PROYEK JALAN LINTAS BAWAH TANAH BUNDERAN MAYJEN SUNGKONO SURABAYA (Magister Teknik Sipil, Fakultas Teknik, Universitas 17 Agustus 1945 Surabaya, 2019)
The underground road construction project in the satellite roundabout area is a project witha risk level that is difficult to predict, so an in-depth risk management analysis is needed.With the approach of the quality, cost and time specs, the dominant risk factors and changesin costs and time will be sought due to the influence of these risk factors. By using 35respondents, it turns out that the final results of the analysis show that from the aspect ofquality, the factor of planning changes, material lacking in quality, low productivity of worktools becomes the dominant risk factor. While from the aspect of time, it turns out that thefailure factor of the team / project management, planning changes, and planning errors arethe dominant risk factors. Meanwhile, in terms of cost aspects of project management factorsand traffic safety, structural excavation, geotextile work, rigid pavement are the dominantrisk factors and from the natural aspect and planning aspects become the dominant source ofrisk in terms of time and scope of structure work, general scope of work of in terms of cost. Asa result of these risk factors, it results in changes in costs for structural works of 75 million or53%, while in public works amounting to 63 million or 11% with changes in time> 30 days. Keywords: Risk analysis, underpass, risk factors, sources of risk